Pengaruh Waktu Ekstraksi Dengan Menggunakan Metode Ultrasonic Assisted Extraction (UAE) Terhadap Aktivitas Antioksidan Ekstrak Daun Duwet (Syzygium cumini) - Marlina Kristina, Clara Vita; Ari Yusasrini, Ni Luh; Yusa, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2022)
This research aims to determine the effect of extraction time on the antioxidant activity of duwet leaf extract and which can produce the highest antioxidant activity in duwet leaf extract. The design used in this study was a Completely Randomized Design (CRD) with treatment consisting 6 levels; 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, and 30 minutes which was repeated 3 times so that it is obtained 18 experimental units. The parameters observed were yield, total phenol, total flavonoids, and antioxidant activity. The data obtained were analizye using variance and if there was a significant effect on the treatment of the observed variables, it was continued with the Duncan Multiple Range Test (DMRT). The results showed that the extraction time of duwet leaf extraction using the Ultrasonic Assisted Extraction method had a significant effect on total phenol, total flavonoids, and antioxidant activity of duwet leaves. The best results were obtained at the extraction time of 25 minutes which has strong antioxidant activity based on the IC50 value of 99.74 ppm, yield 30.24%, total phenol 445.78 mg GAE/g, and total flavonoids 48.90 mg QE/g.